Charlotte's web - Nichols, Charles A.; Takamoto, Iwao.; Reynolds, Debbie; Lynde, Paul.; Gibson, Henry; White, E. B. (Elwyn Brooks), 1899-1985.; Paramount Pictures; Hanna-Barbera Productions; Sagittarius Productions (Firm); Paramount Home Video (Firm) (Hollywood, Calif. : Paramount Home Video, 2001)
Adaptation of E.B. White's novel about Charlotte the spider and her friendship with Wilbur the Pig.
Based on the novel by E.B. White.
Features: interactive menus, scene selection, theatrical trailer, "Meet The Animals" set-top guessing game.
Director of photography, Dick Blundell ... [et al.]; music, Richard M. Sherman, Robert B. Sherman.
Voices: Debbie Reynolds, Paul Lynde, Henry Gibson, and Agnes Moorehead.
MPAA rating: G.
DVD.
Keywords: Swine -- Juvenile drama; Friendship -- Juvenile drama; Spiders -- Juvenile drama; Animated films; Children's films; Films for the hearing impaired; Feature films